2017
DOI: 10.1186/s12911-017-0426-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the reliability of self-reported weight for the management of heart failure: application of fraud detection methods to a randomised trial of telemonitoring

Abstract: BackgroundSince clinical management of heart failure relies on weights that are self-reported by the patient, errors in reporting will negatively impact the ability of health care professionals to offer timely and effective preventive care. Errors might often result from rounding, or more generally from individual preferences for numbers ending in certain digits, such as 0 or 5. We apply fraud detection methods to assess preferences for numbers ending in these digits in order to inform medical decision making.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The SMART study considered end-digit preference in self-reported BP measurements recorded by patients at home, although this was not in the context of a telemonitoring system. 27 Steventon et al 28 found evidence of end-digit preference in weight measures among patients with heart failure using telemonitoring. However, neither study had a comparator group using automatically transmitted data in which there was no possibility of data manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…The SMART study considered end-digit preference in self-reported BP measurements recorded by patients at home, although this was not in the context of a telemonitoring system. 27 Steventon et al 28 found evidence of end-digit preference in weight measures among patients with heart failure using telemonitoring. However, neither study had a comparator group using automatically transmitted data in which there was no possibility of data manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies that did not use Bland-Altman methods have mentioned defined limits. Steventon et al [47] felt that for telemonitoring of heart failure patients, a change of even 2 pounds could be considered important [47]. Bowring et al [48] defined accurate report of height and weight as <2 cm and <2 kg difference between self-report and measured values, based in part on results from Brestoff et al [49].…”
Section: Discussionmentioning
confidence: 99%
“…The literature supports that a weight check for gradual weight change might help clinicians identify those at risk for increased fluid overload from HF decompensation and that such checks might reveal edema and weight fluctuations that sometimes go unnoticed. [9][10][11][12][13] It is not known whether weight checks with every wound care visit would improve wound healing. There is a lack of studies exploring the outcome of weight surveillance and HF management in chronic wound healing.…”
Section: Literature Summary and Gapsmentioning
confidence: 99%
“…Subtle weight changes are associated with early signs of HF exacerbation 9 . Because patients may fail to notice significant lower extremity edema, 10 early symptoms of exacerbation, including weight gain and dyspnea, are red flags for clinicians to educate and encourage self-care 11–13 . Provider failure to engage patients and encourage participation in self-assessment and stigma leading to inaccurate reports of weight can prevent early identification of HF exacerbations, making it more difficult to effectively manage HF in the outpatient setting.…”
Section: Introductionmentioning
confidence: 99%